The Development of Student Worksheets (LKPD) with Contextual Approach to Improve Students’ Science Literature Capabilities - Dwi Agnes Setianingrum; Sabar Nurohman (Journal of Science Education Research, 2022)
The aims of this study: (1) analyze the feasibility of LKPD with a contextual approach, (2) analyze the practicality of LKPD with a contextual approach, (3) analyze the effectiveness of LKPD with a contextual approach to improve students' scientific literacy skills. LKPD with this contextual approach helps students in linking the influence of unhealthy living culture on the health of the excretory organ system in humans. This study uses the Thiagarajan 4D (Four-D Model) development model, consisting of four stages, namely the definition stage, the design stage, and the development stage. The dissemination stage was not carried out, this research was only limited to testing the feasibility and effectiveness of the product. The results showed that: (1) LKPD with a contextual approach was feasible, judging from the results of the material validator 3.54 (very good), the results of the media validator 3.89 (very good), and the results of the teacher validator 3 (very good), ( 2) the results of the analysis of the students' responses are 3.12 (very good), (3) based on the results of the analysis of N-Gain and Effect Size, LKPD with a contextual approach is effective in improving students' scientific literacy skills (N-Gain 0.56 (moderate) Effect Size 1.22 (height)). Based on the analysis of the Paired Sample T Test, there is a significant difference between the pretest and posttest scores.